The Dietary Use of Pigeon Pea for Human and Animal Diets - Belete Kuraz Abebe (The Scientific World Journal)
Pigeon pea (PP) [Cajanus cajan (L.) Huth] plays an important role in preserving poor smallholders’ major source of income in the tropics and subtropics by improving food and feed security, particularly protein intake. In the meantime, protein deficiency is frequent in tropical and subtropical regions due to rapidly increasing human populations and the high cost of animal-origin proteins. As a result, pulse crops should be their primary source of protein. Among these, PP is the most important pulse crop utilized as a food component in rain-fed agricultural conditions with the lowest costs, and it is the best source of protein supplements in typical cereal-based diets to fill the nutritional deficit. Despite this, it is the world’s least-used pulse crop. Therefore, the primary goal of this review was to provide and synthesize scientifically confirmed and up-to-date information on the dietary usage of pigeon pea for food and feed. Protein, carbohydrates, minerals, vitamins, and essential amino acids are all present in reasonable amounts in both mature and immature PP seeds. PP has the most potential for usage as food and feed, and its nutrients are comparable to those of soybeans and maize. PP’s green leaves, roots, seeds, and pods are high in phenolic compounds, which have anti-inflammation, antibacterial, antioxidant, anticarcinogenic, and antidiabetic properties, as well as the ability to cure diseases like measles, smallpox, chicken pox, sickle cell anemia, fever, dysentery, hepatitis, and antimalarial medications for the body. Furthermore, the addition of pigeon pea and its by-products improves ruminant and nonruminant animal feeding performance significantly. In general, PP products such as dried grain, fresh (aerial portion), and green pods are used as a low-cost (low-cost) source of high-quality and quantity of protein food and feed for tropical and subtropical populations’ livelihoods.